(untitled) (OCEM Journal of Management, Technology & Social Sciences, 2026)
Increasing the plastic waste can affect the environment, utilizing the plastic waste generated by incorporating with the bitumen can improve the pavement performance. This approach provides a sustainable solution by reducing landfill accumulation and decreasing reliance on non-renewable resources like natural aggregates and petroleum-based bitumen. The objective of this study is to analyze the cost-effectiveness of using recycled waste materials in asphalt pavement construction by comparing materials and to compare the properties and performance of recycle mixes. Experiments conducted here, explored the feasibility of reusing waste plastic in a productive manner. Paper consistently indicates that when waste plastic is added to hot aggregates, it forms a thin coating over the aggregate particles. Plastic coated aggregate when mixed with bitumen improve the overall performance of the asphalt mix. Results in improved strength, increased resistance to water, weather, and superior long-term performance. Integration of waste with bitumen not only extends, life of pavement but also enhances its smoothness, riding quality, cost-effective and environmentally sustainable. Findings of this study are Plastic additive in asphalt pavement improves strength and flexibility in road construction. It is concluded that such roads enhanced Marshall Stability, and reduced flow values. It is concluded about the, cost- effectiveness, designing and testing of the asphalt pavement along with the road designed by using recycled plastic waste.